PEMBERIAN PRIORITAS PENAMBAHAN GURU SEKOLAH MENENGAH ATAS DI KABUPATEN MAGETAN DENGAN METODE WEIGHTED SUM MODEL - Novia Anggraini; Adi Fajaryanto Cobantoro; Fauzan Masykur (KOMPUTEK, 2022)
Education is one thing that is very mandatory for citizens, especially Indonesia. Apart from clothing, food, shelter, and health, which are other basic needs, education is no less important. The number of teachers is too few to cater for the large number of students, so more teachers are needed. This study aims to give priority to the addition of public high school teachers in Magetan Regency with the Weighted Sum Model method. This research is only limited to being done with a Decision Support System using the Weighted Sum Model method. This research was conducted by collecting data on state high schools in Magetan Regency, East Java Province which was used as an alternative data system and then designing applications using the php and mysql programming languages. This research produces a web- based Expert System Application that implements a Decision Support System with the Weighted Sum Model method. From testing the functionality of the system, the improvement of public high school teachers in Mageten Regency by utilizing the Weighted Sum Model method has succeeded well by 100.